Entering a dream: two days of a native title trial in the north-east Kimberley - A. Reilly (Law Text Culture, 1998)
This article describes the taking of two days of traditional evidence in the Federal Court trial of Ben Ward and Ors on behalf of the Miriuwung and Gajerrong peoples vs. the State of WA and Ors. The applicants filed for the determination of native title in the National Native Title Tribunal in April 1994. After mediation in the Tribunal failed, the application was referred to the Federal Court in January 1995. Initial directions were given by Judge Lee in March 1995, and the taking of traditional evidence occurred between July and October, 1997. The trial at first instance is expected to run until early 1998. It is the first native title hearing to proceed in the Federal Court in Western Australia, and one of the first anywhere on the mainland.